Investigating the high-temperature oxidation mechanisms of carbon steel Q275 - Zou, Rong; Xiao, Xiangtao; Deng, Yong; Shi, Yuanyuan (Frontiers in Materials, 2025)
Q275 carbon steel (0.28–0.38 °C, 0.50–0.80 Mn) is widely used in moderate high-temperature industrial scenarios, but its oxidation behavior at 500–700 °C remains insufficiently clarified; this study aims to address this gap, determine the critical temperature limit for its uncoated application, and provide guidance for high-temperature material selection and protective strategy development. The high-temperature oxidation behavior of Q275 carbon steel was systematically studied via thermogravimetric analysis (for mass change and oxidation kinetics monitoring) and microstructural characterization (for oxide scale morphology, element distribution, and porosity observation) within the 500–700 °C range. The oxidation kinetics of Q275 carbon steel follow a parabolic rate law, with rate constants strongly dependent on temperature; at 500 °C, a dense FeO scale forms (with localized carbon retention up to 8.9 at.%) showing good protective performance, while at 600 °C, Mn segregation at grain boundaries (3.2 wt.%) leads to lamellar (Mn, Fe)O structures and accelerated oxidation, and at 700 °C, cation vacancy percolation results in a porous FeO layer (35% porosity) overlain by Fe2O3 needles, causing rapid mass gain and eventual spallation, with a calculated oxidation activation energy of 104.2 kJ/mol. This activation energy confirms cation vacancy diffusion as the rate-limiting step of oxidation in the 500-700 °C range, and combined with microstructural and kinetic results, 600 °C is identified as the critical temperature limit for uncoated Q275 carbon steel—below 600 °C (e.g., 500 °C) the dense FeO scale provides effective protection, while at and above 600 °C, Mn segregation (600 °C) or cation vacancy-induced porosity (700 °C) causes accelerated oxidation and degradation, making uncoated application risky; these findings lay a foundation for optimizing the steel’s service temperature range and developing targeted protective coatings.